Pengaruh Ekstrak Biji Kopi Robusta Terhadap Histopatologi Duodenum Yang Diinduksi Monosodium Glutamat Pada Tikus Sprague-dawley - Yahmal, Putri Nur'aini (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2024)
Background: Excessive consumption of monosodium glutamate can disturb digestive tract such as the duodenum. Coffee beans contain caffeine, chlorogenic acid, trigonelin, kafestol, kahweol, melanoidin, and N-methylpyridinium. Its antioxidant potential protects rats from damage to duodenal mucosal epithelium by monosodium glutamate 4 g/kgBB. Objective: To determine the effect of Robusta coffee bean extract on monosodium glutamate-induced duodenum histopatology in Sprague-dawley rats. Method: Experimental research with a post test only control group design that for 14 days intervention. The samples were divided into five groups, two control groups and three intervention groups. The calculation of epithelial damage by manual counting assisted by imageJ 2011 software in 1 slice of each sample with microscope in 40x magnification. Results: One Way ANOVA test available p value = 0.005 (p <0.05). Post Hoc LSD test on duodenal epithelial damage score showed a significant difference (p<0.05) between K- and K+ (p=0.001), K+ and P2 (p=0.004), K+ and P3 (p=0.002). Conclusion: There is an effect of Robusta coffee bean extract on monosodium glutamate-induced duodenum histopatology in Sprague-dawley rats.